Peranan Financial Technology dan Literacy Keuangan Untuk Meningkatkan Kinerja Keuangan UMKM di Wilayah Malang - Djoewita Djoewita; Puji Handayati; Satia Nur Maharani (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The financial performance of key MSMEs is to be improved over time. Financial literacy is a determining factor to directly improve the use of financial technology and financial performance of MSMEs. Financial control moderates the effect of financial technology on financial performance, when MSMEs have strong financial control, optimal use of financial technology will further improve the financial performance of MSMEs. Financial institutions can also prioritise the development of financial literacy and education programmes to support MSME actors in achieving better financial outcomes.